Pengembangan Sistem Akuntansi Penggajian Pada Autumn PetShop - Aditya, Mohamad Ragil; Simanjutak, Denis Andreas; Azziky, Muhammad Daffa; Paden, Oktavianus; Syahbani, Muhammad Fahri; Fauziyah, Fauziyah (LPPM Universitas Bina Sarana Informatika, 2024)
The rapid advancement in information technology is evident through the continuous updates in both software and hardware, impacting the performance of computer systems. The role of computers involves the processing, storage, and display of data. Every organization or business entity always requires human resources, referring to employees in this context. Autumn Petshop is a business specializing in the sale of pet food and accessories, and it employs individuals who work at Autumn Petshop. Therefore, a study was conducted on Autumn Petshop regarding its payroll accounting system. The utilization of a web-based payroll accounting system offers several significant advantages for the company as it can enhance the ease and speed of the payroll process for Autumn Petshop employees.